235k views
3 votes
Solve 6^(4x+1)=5^(x-3) for x

Solve 6^(4x+1)=5^(x-3) for x-example-1

2 Answers

3 votes

Answer: The answer is C

Explanation:

User Kolosy
by
5.5k points
5 votes


6^(4x+1)=5^(x-3)\\\\\log6^(4x+1)=\log5^(x-3)\\\\(4x+1)\log 6=(x-3)\log 5\\\\(4x+1)\log 6-(x-3)\log 5=0\\\\4x\log 6+\log 6-x\log 5+3\log 5=0\\\\4x\log 6-x\log 5 = -3\log 5-\log 6\\\\x(4\log 6-\log 5) = -3\log 5-\log 6\\\\x=(-3\log 5-\log 6)/(4\log 6-\log 5)\\\\x=(3\log 5+\log 6)/(\log 5-4\log 6)

User Cama
by
5.4k points